Cadmium and high temperature effects on brain and behaviour of Lymantria dispar L. caterpillars originating from polluted and less-polluted forests. (October 2017) - Perić-Mataruga, Vesna; Petković, Branka; Ilijin, Larisa; Mrdaković, Marija; Dronjak Čučaković, Slađana; Todorović, Dajana; Vlahović, Milena
Abstract: Insects brain as a part of nervous system is the first-line of fast stress response that integrate stress signals to regulate all aspects of insect physiology and behaviour. The cadmium (Cd) bioaccumulation factor (BF), activity of the neurotoxicity biomarker acetylcholinesterase (AChE), dopamine content, expression and amount of Hsp70 in the brain and locomotor activity were evaluated in the 4th instar of Lymantria dispar L. caterpillars fed a Cd supplemented diet and reared in an optimal temperature regime (23 °C) and/or exposed to high temperature (28 °C). The insects originated from two forests, one close to "Nikola Tesla" thermoelectric power plant, Obrenovac (polluted population), and the other Kosmaj mountain (less-polluted population, far from any industrial region). The Cd BF was higher in the less-polluted than in the polluted population especially at the high ambient temperature. AChE activity and dopamine content were changed in the brains of L. dispar from both populations in the same manner. Hsp70 concentration in caterpillar brains showed opposite trends, a decrease in the less-polluted and an increase in the polluted population. Locomotor activity was modified in both Lymantria dispar populations, but the pattern of changes depended on the stressors and their combined effect. ACh activity and dopamine content are sensitive parameters to Cd exposure, regardless of pollutant experience, and might be promising biomarkers in monitoring forest ecosystems. Graphical abstract: Highlights: Bioaccumulation of Cd was higher in brains of less-polluted than polluted population. 28 °C intensified Cd bioaccumulation in less-polluted, but not in polluted population. Brain AChE activity and dopamine content tended to increase in stress conditions. Brain Hsp70 amount decreased in the less-polluted and increased in polluted population. The locomotor activity depended on the stressors and their mutual interaction.